Comparing eDNA metabarcoding and species collection for documenting Arctic metazoan biodiversity. Issue 4 (17th October 2019) - Leduc, Noémie; Lacoursière‐Roussel, Anaïs; Howland, Kimberly L.; Archambault, Philippe; Sevellec, Maelle; Normandeau, Eric; Dispas, Antoine; Winkler, Gesche; McKindsey, Christopher W.; Simard, Nathalie; Bernatchez, Louis
Abstract: Background: Arctic biodiversity has long been poorly documented and is now facing rapid transformations due to ongoing climate change and other impacts, including shipping activities. These changes are placing marine coastal invertebrate communities at greater risk, especially in sensitive areas such as commercial ports. Preserving biodiversity is a significant challenge, going far beyond the protection of charismatic species and involving suitable knowledge of the spatiotemporal organization of species. Therefore, knowledge of alpha, beta, and gamma biodiversity is of great importance to achieve this objective, particularly when partnered with new cost‐effective approaches to monitor biodiversity. Method and results: This study compares metabarcoding of COI mitochondrial and 18S rRNA genes from environmental DNA (eDNA) water samples with standard invertebrate species collection methods to document community patterns at multiple spatial scales. Water samples (250 ml) were collected at three different depths within three Canadian Arctic ports: Churchill, MB; Iqaluit, NU; and Deception Bay, QC. From these samples, 202 genera distributed across more than 15 phyla were detected using eDNA metabarcoding, of which only 9%–15% were also identified through species collection at the same sites. Significant differences in taxonomic richness and community composition were observed between eDNA and species collections at both local and regional scales. This study shows that eDNA dispersion in the Arctic Ocean reduces beta diversity in comparison with species collections while emphasizing the importance of pelagic life stages for eDNA detection. Conclusion: The study also highlights the potential of eDNA metabarcoding to assess large‐scale Arctic marine invertebrate diversity while emphasizing that eDNA and species collection should be considered as complementary tools to provide a more holistic picture of coastal marine invertebrate communities. Abstract : Arctic biodiversity is facing rapid transformations due to ongoing climate change and other impacts including shipping activities, and these changes are placing marine coastal invertebrate communities at greater risk. Environmental DNA (eDNA) metabarcoding could be a revolutionary tool for filling the gaps in species distribution data of coastal ecosystems. In this study, we contrast patterns of biodiversity at different spatial scales revealed by eDNA metabarcoding and conventional species among three harbors from the Canadian Arctic.